Object tracking as the basis of the activity of the operator of an unmanned aircraft complex - Sapozhnikov, Valery O. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The main operation performed by the operator in the human-machine-environment system is tracking, carried out by means of a visual analyser. Increased automation of aircraft control has led to the dominance of automatic flight modes, making manual control redundant, which complicates the operator’s activities, due to the inevitable increase in indicative devices that require control. The absence of tactile perception deprives the operator of an additional channel for obtaining information, creating specific conditions for professional activity. The technical characteristics of an unmanned aerial vehicle, the ergonomics of the workplace and the specifics of the tasks performed determine the list of professionally important qualities of the operator necessary for successful professional activity. The main ones are emotional stability, personal characterological features, the level of motivation, the degree of development of spatial imagination and generalisation, the properties of attention, memory, nonverbal intelligence, thinking, sensorimotor skills and eyesight.
Keywords: tracking; object tracking; automation; autopilot; motivation; thinking; attention properties; memory; nonverbal intelligence; emotional stability; sensorimotor skill; combined operator activity